Effects of cultivar, maturity stage and Ethrel treatment on ripening and fruit quality of tomato (Solanum lycopersicum L.) - Elkashif, Mohamed E (Gezira Journal of Agricultural Science; Vol 12 No 1 (2014), 2014)
This study was conducted with the objective of determining the effects of maturity stage at harvest and Ethrel treatment on ripening and fruit quality of selected tomato cultivars. The experiment was conducted in the laboratory of biochemistry at the Faculty of Agricultural Sciences, University of Gezira, Wad Medani, Sudan, during the seasons 2009/10 and 2010/11. Cultivars used were Vt 925, Castle Rock and Peto 86. Maturity stages were mature green and breaker. Ethrel treatments were 0 ml/L and 2 ml/L. Treatments were arranged in a completely randomized design with three replicates. Results  showed that the cultivar Vt 925 had the largest fruits and the highest ascorbic acid and TSS contents as compared to the other two cultivars in both seasons. Results also showed that advancement of maturity stage significantly decreased fruit green life in both seasons, however, total soluble solids were slightly increased with an increase in tomato fruit maturity stage. Titratable acidity decreased slightly with the  advancement of maturity stage. Fruit maturity stage had no significant effects on ascorbic acid content in both seasons. Ethrel treatment significantly increased uniformity of ripening and ascorbic acid content, but decreased fruit green life in both seasons, however, it had no significant effects on TSS and acidity. It is recommended to grow the cultivar Vt 925, harvest fruits at the mature green stage and treat them with Ethrel at destination markets in order to achieve uniformity of ripening, to extend their shelf life and end up with high fruit quality.       تأثير الصنف وطور النضج والمعاملة بالإثرل على إنضاج ونوعية ثمار الطماطم  ( Solanum lycopersicum L.) محمد الحاج الكاشف و مشاعر سالم حسين و عثمان محمد الامين   كلية العلوم الزراعية ، جامعة الجزيرة ، واد مدني ، السودان   الخلاصة        تهدف هذه الدراسة لتحديد أثر الصنف وطور النضج والمعاملة بالإثرل على نضج ونوعية ثمار الطماطم. أجريت التجربة بكلية العلوم الزراعية، جامعة الجزيرة، ود مدني، السودان، خلال موسمي 10/2009 و11/ 2010 الأصناف المستخدمة هي Vt925، Castle Rock، Peto 86، تم الحصاد في طوري البلوغ الاخضر والنجمة وكانت تراكيز الاثرل المستخدم هي 0 ml و 2ml/L. نظمت المعاملات بالتصميم العشوائي الكامل بثلاث مكررات. تمت دراسة الصفات الفيزيائية والكيميائية لثمار الطماطم وقد أوضحت النتائج أن الصنف Vt925 أنتج ثمارا أكبر حجماً وتحتوي على أعلى نسبة من فيتامين ج   (Ascorbic acid) والمواد الصلبة الذائبة (TSS) مقارنة مع الأصناف الأخرى للموسمين معاً. حصاد الثمار في طور النجمة أدى لنقص معنوي في عدد الأيام اللازمة للوصول لطور النضج، كما أدى لزيادة ملحوظة في محتوى الثمار من المواد الصلبة الذائبة مما ادي لنقص طفيف في حمض الستريك (Citric acid)، معاملة الثمار بالإثرل أدى لزيادة معنوية في نسبة تجانس النضج و محتوى الثمار من فايتامين ج ، كما أدى لنقص معنوي في عدد الأيام اللازمة للوصول لطور النضج فيما لم يؤثر على محتوى الثمار من المواد الصلبة الذائبة وحمض الستريك. يوصى بزراعة الصنف Vt925 على أن يتم الحصاد في طور البلوغ الاخضر وتعامل الثمار بالإثرل لإطالة العمر التخزيني والمحافظة على جودة الثمار.